(3JUMjM GdJUMja hJMQjQ GdJMQjas - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dGjZdWI GNJdGa hHYO aEf GdJUMja hGdJMQja bdeG Sde efgeG cHjQ Ch fLG efgeG Ph GJbGf s
(3BNQgG (B:s
(3BNQ GdehLhO Cbhdg hChQO hQO heYfi jhTc jSQY s
(3GdfSNI HGgJIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs